Excavations on Iona, 1979 - Barber, John W; Bohncke, S; Fairweather, A; Groenman-van-Waateringe, W; Lehane, D; McCormick, F; Máté, I; Richardson, H; Strong, P (Proceedings of the Society of Antiquaries of Scotland, 1982)